(untitled) (Bangladesh Journal of Botany, 2018)
Ultraviolet radiation in the C band to limit storage losses of potato was applied. Six edible potato varieties, viz., Lord, Vineta, Owacja, Ditta, Finezja and Tajfun were used as test materials. UV-C radiation was emitted from a 15 W radiator. The wavelength of the light used to irradiate potato tubers was 253,7 nm and the power density from 80 to 100 μW/cm2. The method of reduction of storage losses of potato tubers, based on their exposure to UV-C irradiation, can complement the presently used methods of potato crop protection during long-term storage.